Defining and Pursuing Goals in a Work First Environment: An Analysis of Public Assistance Recipients' Experience and Perception of Public Policy on the Frontlines. Issue 1 (1st January 2021) - Dunford-Stenger, Amy; Holcomb, Stephanie; Hetling, Andrea; Krepcio, Kathy
ABSTRACT: For many public assistance recipients, engaging in work activities is mandatory to receive benefits. Although the goal of such activities, to assist recipients in finding employment quickly, matches the goal of many recipients, research indicates that few obtain long-term employment. Informed by earlier welfare studies and street-level organization theory, we conducted focus groups to understand recipients' experiences and perceptions of the relationship between frontline public policies and their employment-related goals. Our findings reveal that recipients perceive rules and services as mismatched with their needs and experience poor communication with staff, leaving them to advocate for themselves and impeding progress.